2015
DOI: 10.1128/jcm.01013-15
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of the RNA-Based Aptima Human Papillomavirus (HPV) Assay and the DNA-Based Hybrid Capture 2 HPV Test in a Routine Screening Population of Women Aged 30 to 60 Years in Germany

Abstract: f Testing for E6/E7 mRNA in cells infected with high-risk (HR) human papillomavirus (HPV) might improve the specificity of HPV testing for the identification of cervical precancerous lesions. Here we compared the RNA-based Aptima HPV (AHPV) assay (Hologic) and the DNA-based Hybrid Capture 2 (HC2) HPV test (Qiagen) to liquid-based cytology (LBC) for women undergoing routine cervical screening. A total of 10,040 women, 30 to 60 years of age, were invited to participate in the study, 9,451 of whom were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 35 publications
10
85
0
1
Order By: Relevance
“…The agreement between the two tests for the detection of HR HPV was also very high (Table ). Our observed sensitivity rates of both tests were similar to that of previously reported findings in referral and screening populations for detection of CIN2+ [Monsonego et al, ; Ratnam et al, ; Szarewski et al, ; Iftner et al, ]. Of the 396 cases of cervical cancer included in the study, the assays yielded discrepant results in only 11 (2.8%) cases, and were negative in 14 (3.5%) cases, indicating a very high level of sensitivity of both assays in detecting invasive cervical cancer (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…The agreement between the two tests for the detection of HR HPV was also very high (Table ). Our observed sensitivity rates of both tests were similar to that of previously reported findings in referral and screening populations for detection of CIN2+ [Monsonego et al, ; Ratnam et al, ; Szarewski et al, ; Iftner et al, ]. Of the 396 cases of cervical cancer included in the study, the assays yielded discrepant results in only 11 (2.8%) cases, and were negative in 14 (3.5%) cases, indicating a very high level of sensitivity of both assays in detecting invasive cervical cancer (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the high NPV (99.7%, 95% CI: 99.6–99.9) that was reported 6 years after negative HPV‐DNA testing in a joint European randomized screening trial . Furthermore, preliminary results after 6 years of follow‐up of 872 women with normal cytology, and with negative HPV‐mRNA and negative hybrid capture II test (Qiagen) at baseline demonstrated high NPV of 99.77% (95% CI; 99.1–99.9) and 99.85% (95% CI; 99.1–99.9) for absence of CIN3, respectively …”
Section: Discussionsupporting
confidence: 85%
“…This brings into focus the question of whether the management recommendations for HPV-positive women should be the same irrespective of which assay detected the infection. Studies agree in that, regardless of the assay used for primary screening, HPV-positive women should not be directly referred for colposcopy (2628). For HC2-positive women from the Dutch VUSA-screen study, Rijkaart and colleagues proposed using cytological triage and to repeat cytology testing at 12 months postbaseline for triage-negative women (26).…”
Section: Discussionmentioning
confidence: 99%
“…In this setup, the addition of HPV genotyping would lead to a higher cumulative number of colposcopies but would not significantly decrease the risk of missing ≥CIN3 cases. On the other hand, Iftner and colleagues, using data from the German Aptima- and HC2-based screening study (27), and Wright and colleagues, using data from the U.S.-based ATHENA study evaluating the cobas assay (28), found that optimal triage strategies seemed to involve HPV 16/18 genotyping at baseline. In these two studies, follow-up testing of triage-negative women could not be further evaluated, as immediate colposcopy was recommended to all HPV-positive women (for study purposes).…”
Section: Discussionmentioning
confidence: 99%